A Cycle of Integrated Lessons of Literature and World Art Culture Dedicated to The Work of S.A. Yesenin - Khudaiberdieva Dilfuza Mukhtarovna (Periodica Journal, 2023)
The topic under study is relevant due to the fact that the integrated lesson aims to lay the foundations for a holistic view of nature and society, and to form one's own attitude to the laws of their development. Regarding this work, we can say that using the possibilities of the subject "World Artistic Culture" will improve the perception of the material studied in the lessons dedicated to Sergei Yesenin. Pictures, musical inserts, illustrations help to better perceive the material, develop the imagination of students. The purpose of this article is to show the connection between the subjects "world art culture" and "literature" on the basis of an integrated lesson on the topic of S.A. Yesenin.
Keywords: aesthetic development; personality; influence; artistic development